Treatment of odontogenic myxoma in upper maxillary. A case report - Moreno Villalobos, David Erik (2021)
Odontogenic myxoma is a locally aggressive benign neoplasm with a low prevalence (frequency 2% to 5% of odontogenic tumors) in the jaws. This tumor often presents as an asymptomatic expansive lesion without sensory nerve changes. The aim of this study is to detail the case of a 42-year-old male patient who attends the Oral and Maxillofacial Surgery service of the Hipólito Unanue National Hospital due to a slow-growing tumor in the upper jaw, which increased in size over time and displacing dental organs, and extending to the hard palate and part of the soft palate, the pathological diagnosis was odontogenic myxoma and received radical treatment (hemimaxilectomy) due to the aggressive nature of the tumor. In this work we discuss the presentation of odontogenic myxoma in the maxilla, treatment approaches; detailing the importance of proposing treatment alternatives that allow immediate reconstruction generating the least possible morbidity.